Preparation and Characterization of Fe3O4/Ethiodized-oil Magnetic Fluids Used in Arterial Embolization Hyperthermia - 罗志 王益明 洪若瑜 李洪钟 (Chinese journal of chemistry, 2012)
Fe3O4 nanoparticles （NPs） were prepared by the co-precipitation of Fe3＋ and Fe2＋ with ammonium hydroxide, and were modified by four different surfactants. The modified Fe3O4 NPs were characterized by Fourier transform infrared spectroscopy, X-ray powder diffraction, transmission electron microscopy and vibrating sample magne- tometer. Then, the modified Fe3O4 NPs were dispersed in ethiodized-oil by mechanical agitation and ultrasonic vi- bration to obtain stable Fe3O4 /ethiodized-oil magnetic fluids （MFs）. The magnetic properties and rheological prop- erties of the MFs were measured using a Gouy magnetic balance and a rotational rheometer, respectively. The satu- ration magnetization of the Fe3O4 modified by oleic acid was 52.1 Emu/g. Furthermore, the result showed that the inductive heating effect of oleic acid stabilized Fe3O4/ethiodized-oil MF was remarkable and it only took 650 s for the temperature rising from 25 ℃ to 65 ℃. The specific absorption rate of the MF was 50.16 W/（g of Fe）. It had a potential application in arterial embolization hyperthermia.